1993
DOI: 10.1093/hmg/2.11.1871
|View full text |Cite
|
Sign up to set email alerts
|

Iduronate-2-sulfatase gene mutations in 16 patients with mucopolysaccharidosis type II (Hunter syndrome)

Abstract: Mutations of the iduronate-2-sulfatase gene were identified in 16 patients with mucopolysaccharidosis type II (Hunter syndrome). Together with another 10 cases reported by us earlier it emerges that about 20% of the patients have deletions of the whole gene or other major structural alterations. One, two or three base pair deletions are found in about 23% of the cases while the remaining about 57% carry point mutations predicting amino acid replacement, premature termination of translation, or aberrant splicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 0 publications
6
23
0
2
Order By: Relevance
“…Whilst about 80% of them carry point mutations or small deletions/ insertions, 6,13,14,16 the remaining 20% have large structural rearrangements. Two out of 44 German patients carry an inversion (4.5%), another three deletions of the whole gene (6.8%), ie 11.3% in total have gross rearrangements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst about 80% of them carry point mutations or small deletions/ insertions, 6,13,14,16 the remaining 20% have large structural rearrangements. Two out of 44 German patients carry an inversion (4.5%), another three deletions of the whole gene (6.8%), ie 11.3% in total have gross rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of exons was done with intron-specific primers as described previously. 6,14 IDS exon 3-forward and exon 8-reverse primers were used to generate a 2.8 kb junction fragment that included both the proximal breakpoints of inversions and internal deletion breakpoints. Primers IDS62 and IDS63 (similar to 60033-F and 58740-B in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Ten fragments of the I2S gene, exons and exon/intron boundaries, were amplified by polymerase chain reaction (PCR) using primers listed in Table 2 (Bunge et al 1993;Rathmann et al 1996;Isogai et al 1998;Gort et al 1998). The PCR reaction was carried out in a total volume of 50 ll containing 1.25 units of ExTaq polymerase, 10 nmol dNTPs, genomic DNA (100 ng), and Liver size on physical examination f I2S activity enzymatic activity of iduronate-2-sulfatase g nd not detectable; detection limit of the experiment was 1.6 nmol/mg protein/4 h; normal range 58.4-114 nmol/mg protein/4 h the respective primers (0.5-2.0 lM).…”
Section: Dna Preparation and Sequencingmentioning
confidence: 99%
“…The G374G does not change amino acids; however, it is considered to activate a cryptic splice site resulting in an in-frame deletion of 20 amino acids, E375-G394 (Bunge et al 1993). The authors suggested that the mutant with this deletion should preserve its enzymatic activity because the deletion occurred in the long nonconserved region among the sulfatase family (Bunge et al 1993).…”
Section: Mutations Found In the Attenuated Phenotypementioning
confidence: 99%
“…When both assays are used, heterozygosity of close to 50% is expected. 26 Another coding polymorphism located in the iduronate-2-sulfatase (IDS) gene (C/T 438) 27 has also proven to be useful in the study of clonal hematopoietic disorders. 28 Although these assays are substantially less informative than the HUMARA assay, they have the theoretical advantage of not relying on methylation pattern to assess the activity of the X-chromosome, since they directly rely on the exclusive transcriptional activity of the active X-chromosome.…”
Section: The Development Of Newer More Informative Xinactivation-basmentioning
confidence: 99%